Student Perspective about Traditional Process and Formative Evaluation. Group Contrasts in the same Subjects - Hortigüela, David; Pérez Pueyo, Ángel; Abella, Víctor (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2015)
This study, with a sample of 357 students in 4 subjects at the University of Burgos (Spain), contrasts the perception of students about the assessment received, focusing on the difficulties encountered in the process and the level of involvement and monitoring performed. In each subject, a group has been evaluated using a traditional and another system using formative assessment. The questionnaire used was the scale of assessment systems on initial training. The working methodology was quantitative, using both a descriptive analysis (percentages) and inferential (contingency tables and ?2) depending on the extracted factors. The results reflect a more favorable perception in the groups that received a formative assessment, recognizing that the system is more complex but allows more feedback to the teacher, which results in greater involvement and a more meaningful learning.